2016
DOI: 10.1002/1873-3468.12341
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycosylation in the thermoacidophilic archaeon Sulfolobus acidocaldarius involves a short dolichol pyrophosphate carrier

Abstract: N-glycosylation is a post-translational modification that occurs across evolution. In the thermoacidophilic archaea Sulfolobus acidocaldarius, glycoproteins are modified by an N-linked tri-branched hexasaccharide reminiscent of the N-glycans assembled in Eukarya. Previously, hexose-bearing dolichol phosphate was detected in a S. acidocaldarius Bligh-Dyer lipid extract. Here, we used a specialized protocol for extracting lipid-linked oligosaccharides to detect a dolichol pyrophosphate bearing the intact hexasac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In fact, two recent studies confirmed the presence of the DolPP-linked N -glycans in Sulfolobales (Guan et al 2016; Taguchi et al 2016). Interestingly the study of Taguchi et al underlined the difference of the lipid carrier between cren- and euryarchaea, as in all analysed euryarchaea DolP-linked oligosaccharides were present, whereas in the crenarchaea P. calidifontis and S. solfataricus lipid-linked oligosaccharides were assembled on DolPP backbone (Taguchi et al 2016).…”
Section: Discussionmentioning
confidence: 81%
“…In fact, two recent studies confirmed the presence of the DolPP-linked N -glycans in Sulfolobales (Guan et al 2016; Taguchi et al 2016). Interestingly the study of Taguchi et al underlined the difference of the lipid carrier between cren- and euryarchaea, as in all analysed euryarchaea DolP-linked oligosaccharides were present, whereas in the crenarchaea P. calidifontis and S. solfataricus lipid-linked oligosaccharides were assembled on DolPP backbone (Taguchi et al 2016).…”
Section: Discussionmentioning
confidence: 81%
“…In yet another halophilic archaea, Halobacterium salinarum (optimal growth in 3.9 M NaCl [30]), the surface (S)-layer glycoprotein, the building block of the S-layer surrounding the cell, is simultaneously modified by two distinct N-linked glycans, one initially assembled on DolP, the second on DolPP [31,32]. In the thermoacidophile Sulfolobus acidocaldarius (optimal growth at 80°C and pH 2 [33]), DolPP is charged with the same hexasaccharide as N-linked to glycoproteins in this organism, as well as its derivatives, although DolP and hexose-charged DolP have also been detected [34,35]. In the related species Sulfolobus solfataricus (optimal growth at 87°C and pH 3.5–5 [36]), DolPP is charged with the first six sugars of the heptasaccharide N-linked to glycoproteins in this organism; the final sugar could thus be derived from hexose-charged DolP [37].…”
Section: The Lipid Glycan Carriers Of N-glycosylation Across Evolumentioning
confidence: 99%
“…While both contain up to 25 isoprene subunits and present a hydroxyl group at the so-called α end, dolichols include a saturated α position isoprene subunit, whereas polyprenols, including C 55 undecaprenol, do not. The dolichols used in eukaryal N-glycosylation can, however, be distinguished from their archaeal counterparts in that all of the dolichols shown to participate in archaeal N-glycosylation to date also present an additional saturated isoprene subunit at the ω position, namely that isoprene farthest from the α end of the molecule [27,29,32,34,35,37,40,41]. The significance of saturation of the ω position isoprene is not clear, since in vitro studies revealed how C 55,60 DolP saturated solely at the α position could be glycan-charged using enzymes involved in N-glycosylation in the methanogen Methanococcus voltae (grown in the laboratory in a 80%H 2 /20% CO 2 atmosphere [42]).…”
Section: The Lipid Glycan Carriers Of N-glycosylation Across Evolumentioning
confidence: 99%
“…In addition, the dolichol carrier normally recognized by AglB in S . acidocaldarius was recently shown to be an unusual, short (C 45 ) dolichol pyrophosphate [30] and not the dolichol phosphate initially believed to serve as the glycan lipid carrier [28] and this could cause recognition problems for the S . acidocaldarius AglB towards the Mc .…”
Section: Resultsmentioning
confidence: 99%
“…In different archaea, the sugar linking the glycan to the asparagine of the target protein can be N -acetyl-glucosamine, N -acetyl-galactosamine or a simple hexose [1]. The lipid carrier has been identified in several archaea and can be dolichol phosphate or dolichol diphosphate and the dolichol can vary in length as well as degree of saturation [2,24,2630]. These are all aspects that may affect AglB activity.…”
Section: Introductionmentioning
confidence: 99%